A Family of Optimal Eighth Order Iteration Functions for Multiple Roots and Its Dynamics. (15th March 2021) - Akram, Saima; Akram, Faiza; Junjua, Moin-ud-Din; Arshad, Misbah; Afzal, Tariq
Abstract : In this manuscript, we present a new general family of optimal iterative methods for finding multiple roots of nonlinear equations with known multiplicity using weight functions. An extensive convergence analysis is presented to verify the optimal eighth order convergence of the new family. Some special cases of the family are also presented which require only three functions and one derivative evaluation at each iteration to reach optimal eighth order convergence. A variety of numerical test functions along with some real-world problems such as beam designing model and Van der Waals' equation of state are presented to ensure that the newly developed family efficiently competes with the other existing methods. The dynamical analysis of the proposed methods is also presented to validate the theoretical results by using graphical tools, termed as the basins of attraction.